One perfect lie - Scottoline, Lisa (New York : St. Martin's Press, 2017)
"One Perfect Lie is an emotional thriller and a suburban crime story that will keep you guessing until you turn the very last page. On the surface, it tells the tale of the struggling single mother of a high-school pitcher, a shy kid so athletically talented that he's being recruited for a full-ride scholarship to a Division I college, with a future in major-league baseball. But the mother fears that she's losing her grip on her son because he's being lured down a darker path by one of his teammates, a secretly disturbed young man from an affluent family, whose excellent grades and fun-loving manner conceal his violent criminal plans. Add a handsome stranger who comes to town and infiltrates the high school, posing as a teacher but with a hidden agenda all his own. The mix becomes combustible when a beloved faculty member turns up dead as a suicide, in circumstances equally consistent with murder. Only then is the true identity of the fake teacher revealed, and the single mother finds herself engaged in a battle for the future, the soul, and the very life of her only son. One Perfect Lie is a riveting and suspenseful family drama, and by the time you close the book, you will realize that nothing was as it seemed at the beginning"--
Keywords: FICTION / Suspense; FICTION / Thrillers; Suspense fiction